Screenwriting is rewriting : The Art and Craft of Professional Revision - Epps, Jack (New York [etc.] Bloomsbury, 2016)
"If there is one skill that separates the professional screenwriter from the amateur, it is his or her ability to rewrite successfully. But rewriting can be confusing and difficult even for the most battle-hardened screenwriter. From the screenwriter of Top Gun, Dick Tracy and The Secret of My Success comes a comprehensive guide that explores the art and craft of rewriting. Jack Epps, Jr. guides the writer to identify the weaknesses in his screenplay by using the pass method to solve individual story or character problems one at a time, rather than the common model of trying to fix everything in one giant rewrite, by taking the writer on a journey from First Draft to Final Polish. With Screenwriting is Rewriting, Epps gives practical tips on organizing notes, creating a game plan, and then executing a series of precision focused passes that address the major story, character and plot issues. He includes sample notes, game plans and beat sheets from the his own work on films such as Sister Act, Tootsie and Top Gun. Also included are exclusive interviews about rewriting with screenwriting masters Robert Towne (Chinatown), Frank Pierson (Dog Day Afternoon), and Susannah Grant (Erin Brockovich), and a companion website containing an instructor's guide for a 10 week term or 16 week semester"-- Provided by publisher
Keywords: Guiones cinematográficos